Animal welfare and ethics - Gere, Tibor (Animal welfare, Ethology and Housing Systems (AWETH), 2008)
Through his presentation the author would like to express his honours towards those animals which have been subject of and participated in his scientific research programmer for many decades and thus have contributed to the success of his research work and to the establishment of new research results in the field of livestock management, animal genetics, ethology, production biology, gastrophysiology, biotechnology and molecular genetics. In his study the author offers a historical survey on the development of views concerning animal welfare and animal ethics. He discusses in details the philosophic and legal standpoints related to the legal status of humans and animals. He mentions the harmful effects of the circumstances that industrial production methods have established. He also gives an account on the perception summarizing animal rights, put into words at the first time ever by the Farm Animal Welfare Advisory Committee. Similarities and differences of human and animal rights are also discussed, as well as the ethical perception and moral foundations of animal protection movements of the recent era. He reviews the relations between biotechnics and animal ethics, the possible human and animal welfare consequences of biotechnical revolution and related extremist points of view. He demonstrates the perception of the most significant world religions on the relation of humans and animals. Finally, the author casts his vote for the necessity of legal regulation by act on the protection and utilization of animals.